HUBUNGAN MORAL KERJA DENGAN PELAKSANAAN TUGAS GURU SEBAGAI PENGAJAR DI SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 3 KOTA PADANG - Amelia Syafruddin (Jurnal Bahana Manajemen Pendidikan, 2013)
This research aimed to morale relationship with implementation of task as a teacher of teachers at SMK N 3 Kota Padang. Problem found was caused lack of implementation of task as a teacher of teachers employed moral. The population is employe 73 people and samples is employe 63 people. Large samples are determined based on Proportional Stratified Random Sampling technique using table krijce. Instrument by using is likert scala. Analyzed by correlation technique Product Moment. The results is significant relationship between morale relationship with implementation of task as a teacher of teachers at SMK N 3 Kota Padang. Kata kunci: moral kerja: pelaksanaan tugas guru sebagai pengajar